Isolation and Identification of Dermatophyte Species from Iraqi Patients Using PCR-ITS Regions - Hendi, Aseel Hasan; Al-Araji, Alaa Mohsin (Iraqi Journal of Science, 2025)
Dermatophytes are the primary etiological agents responsible for superficial fungal infections worldwide. The current study, undertaken in Baghdad, Iraq, aimed to diagnose dermatophyte species by targeting the ITS (Internal Transcribed Spacer) region and employing phylogenetic analysis techniques. A total of 104 specimens from hair, nails, and skin scrapings of patients were examined microscopically and cultured on a specific medium SDA with addition of cycloheximide and chloramphenicol. PCR with ITS1 and ITS4 primers was employed for further characterization of dermatophytes. According to results, tinea corporis was the predominant infection (51.9%), and tinea cruris (18.2%). Molecular results revealed that T. indotineae (24%) is the predominant isolate, followed by T. mentagrophyte (5.7%), T. simii (2.8%), T. rubrum, and M. canis (3.8%, 1.9% respectively). This is the first record of T. indotineae affected by tinea corporis and cruris in Baghdad and Iraq. Twelve isolates, including nine T. indotineae, registered with new code in the NCBI database. The findings showed that PCR-ITS methods are essential for monitoring trends in dermatophytosis and detecting dermatophyte species in communities, given the presence of a complete database and operational taxonomic richness and specificity.